Endothelial Dysfunction, Functional Structural Changes in the Vessels in Patients with the Unstable Angina with Arterial Hypertension - Denesiuk O. (Львівський клінічний вісник, 2013)
Introduction. One of the most actual problems of modern cardiology is the study of endothelial function, functional and structural changes in arteries, especially in patients with arterial hypertension (AH), the atherosclerotic process primarily affects the arteries of the elastic type (aorta) and slightly less – of the muscle type (brachial artery). Insufficient studies have been done to diagnose the endothelial function and arterial remodeling in the case of coronary heart disease (CHD), in particular with comorbid hypertension. Aim. To study the endothelial and functional-structural changes in blood vessels in patients with unstable angina (UA) with comorbid hypertension.